Development of motivational and value orientation of personality in physical culture and recreational activities - Kozhokar M.Yu. ,; Elmurzaev M.A. ,; Kostromin O.V. ,; Agaev R.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to reveal the internal psychological mechanisms that motivate individuals to engage in physical and recreational activities. Methods and structure of the study. The methodological basis was built on the intersection of theoretical and empirical approaches based on a comparative analysis of the practice of organizing physical culture and recreational activities. Results and conclusions. The highlighted values of physical culture and recreational activities are general in nature. They may vary in intensity, component content, and hierarchy within an individual's overall system of life values. Social relations undoubtedly play a key role in shaping an individual's motivational and value sphere.